Mixed Migration Review 2020. Highlights, Interviews, Essays, Data. Mixed migration and cities. Urban frontlines for displacement and mobility. - Bauder, Harald; Van Haasen, Sophie; Reitano, Tuesday; Bird, Lucia; Horwood, Chris; Litzkow, Julia; Sadye Wolff, Jessica; Jacobsen, Karen; Grant, Peter; Saunders, Douglas (My University, 2020)
The third publication of the annual Mixed Migration Review by the Mixed Migration Centre focuses on urban migration. This year’s edition offers updates on global mixed migration trends and policy events while examining the role of cities in human mobility. The Keeping track section sets out the year’s key mixed migration trends across the globe and summarises selected policy and legislative developments. A series of essays explore the urban reality of mixed migration, zooming in on topics such as climate change, people smuggling, displacement between and from cities, the global pandemic, the opportunities and risks refugees and migrants encounter in urban areas and more. The report also includes a series of interviews with migration experts, policy makers, academics, and mayors.
Keywords: Migration; Migrationsanalyse; Bevölkerungswanderung; Wanderungsforschung; Wanderungsmotiv; Urbanisierung; Stadtbevölkerung; International; Corona-Krise